Effectiveness of animated video-based group psychoeducation in improving mental health literacy among family caregivers of people with mental disorders - Pahreza Zaka Raihan; Osep Yasier Almunsiri; Lailatul Fadilah; Cucuk Kunang Sari (JOURNAL OF Mental Health Concerns, 2026)
Background: Mental disorders remain a health problem with a high relapse rate in People with Mental Disorders (PWMD), which is influenced by the low level of family mental health knowledge in recognizing signs and symptoms and efforts to prevent relapse. Purpose: To examine the effectiveness of animated video-based group psychoeducation in improving family mental health literacy for relapse prevention among individuals with SMI in the working area Method: A quantitative approach with a quasi-experimental design using a one-group pretest - posttest design was employed. The study involved 40 family members of individuals with SMI. Data were collected using the Mental Health Literacy Scale (MHLS) before and after the intervention. Statistical analysis was conducted using the Paired Samples t-test.   Results: The analysis revealed a statistically significant difference between pretest and posttest scores (p < 0.001), indicating that the intervention had a significant effect on improving family mental health literacy. Conclusion: Animated video-based group psychoeducation is effective in enhancing family mental health literacy for relapse prevention among individuals with SMI. Keywords:  Animated Videos; Group Psychoeducation; MHLS; Mental Health Knowledge; People With Mental Disorders.